Application of modified neck drainage in the management of cervical anastomotic fistula in esophageal cancer patients - Song Wu; Zhe Zhang; Zhonghua Qin (Journal of Cardiothoracic Surgery)
Abstract Background Anastomotic fistula is a rare but life-threatening complication of esophageal cancer, and its treatment remains challenging.We aimed to evaluate the clinical efficacy of modified cervical drainage in the management of cervical anastomotic fistula in patients after esophageal cancer surgery. Methods From June 2017 to December 2021, 25 esophageal cancer patients who developed cervical anastomotic fistula were enrolled in the study. Among them, 14 patients were treated with modified cervical drainage, which served as the observation group, while the remaining 11 patients underwent open incision and drainage, which served as the control group. The treatment outcomes of the two groups were compared and analyzed. Results The observation group had a significantly shorter healing time, fewer dressing changes, shorter hospital stay, and lower hospitalization costs compared to the control group (P < 0.05). The incidence of complications in the neck was not significantly different between the two groups (P > 0.05). All patients resumed a normal diet without experiencing fever, coughing or other discomfort, and were discharged after a smooth recovery. Conclusions Modified neck drainage, as a treatment method for cervical anastomotic leakage in esophageal cancer patients, has preliminarily demonstrated potential in promoting patient recovery. However, its efficacy still requires further validation and confirmation through studies with larger sample sizes. Graphical abstract